STUDI STRATIGRAFI DAN PALEOGEOGRAFI ENDAPAN KENOZOIKUM CEKUNGAN SENGKANG PADA DAERAH KABUPATEN MAROS, PROVINSI SULAWESI SELATAN - Hendry Tri Pradipta Putra; Hadi Nugroho; Yoga Aribowo; Danny Irawan (Geological Engineering E-Journal, 2013)
Stratigraphy and paleogeography study basin sengkang never discussed in detail by earlier researcher, caused by pattern sequence stratigraphy this basin is difficult is determined disturbed consequence by activity tektonic mobile in Paleogen and Neogen. The mentioned that make as object that interesting to studied and studied furthermore.Watchfulness method is done with research method, descriptive method, and analysis method. Research method is done with direct quest at field, this descriptive method is done with describe field data and laboratory data, and analysis method is done with analyze litostratigraphy, biostratigraphy, sequence stratigraphy, and tektonostratigraphy the result is used for discussion syntheses paleogeography watchfulness region.Litostratigraphy watchfulness region is divided to be four rock formations with sequence the position from old to young, that is Mallawa Formation aged Middle Eocene, Tonasa Formation aged Early Miocene, Camba Formation with age turn Late Miocene, and Walanae Formation with age turn Pliocene. From formation, knowable ten species foraminifera planktonic as age areas biostratigraphy, that is Globigerapsis index as datum age zone P.11, Globigerina yeguaensis as datum age zone P.12, Orbulinoides beckmanni as datum age zone P.13, Globigerinoides immaturus as datum age zone N.4, Globoquadrina dehiscens as datum age zone N.5, Orbulina bilobata as datum age zone N.6, Globigerinoides diminutus as datum age zone N.7, Praeorbulina glomerosa as datum age zone N.8, Globigerinoides conglobatus as datum age zone N.18, and Globorotalia crassaformis as datum age zone N.19. Sequence stratigraphy watchfulness region consists of three sequence precipitation that consist of three packages system tract complete, that is highstand system tract, transgressive system tract, and lowstand system tract. Tektonostratigraphy sediment Kenozoikum watchfulness region, got four sequence, that is syn-rift, sag-basin, syn-orogenic, and post-orogenic. History paleogeography watchfulness region since Middle Eocene still environment land-deltaic with precipate formation unit mallawa, then in miosen beginning happen phase transgresi with precipate Mallawa Formation, and Late Miocene to happen regression phase with precipate Camba Formation, and phase transgresi return to happen by the end of Pliocene beginning with precipate Walanae Formation.